LC-MS Analysis of Secondary Metabolites of Asphodelus aestivus Brot. (Asphodelaceae) grown wild in Jordan - El-Elimat, Tamam; Olimat, Suleiman; Ali Agha, Ahmed S.A.; Aburjai, Ahmad; Aburjai, Talal (Jordan Journal of Pharmaceutical Sciences, 2024)
The phytochemical composition of Asphodelus aestivus Brot., a plant with therapeutic properties in traditional medicine, remains largely unexplored, particularly in the specific environmental conditions of Jordan. This study utilized advanced LC-MS techniques to comprehensively analyze the secondary metabolites of a plant species endemic to Jordan. The development of the LC-MS method involved optimizing parameters such as solvent composition, gradient elution, and ionization techniques to achieve comprehensive metabolite profiling. The method was validated to ensure accurate, precise, sensitive, and specific identification and quantification of the compounds. Our analysis identified seven distinct compounds, including both familiar molecules and more complex anthrones and glycosides. This finding emphasizes the wide range of chemical compounds found in the plant and highlights the distinct chemical variations influenced by regional environmental factors. These findings contribute to our understanding of Asphodelus aestivus Brot. and highlight the potential therapeutic uses of its distinct phytochemical composition. This research makes a significant contribution to the field of plant-based natural products by combining modern analytical methods with traditional medicinal knowledge to investigate the complex phytochemical composition of Asphodelus aestivus.